Theoretical exploration of novel catalyst support materials for fuel cell applications. Issue 39 (20th September 2016) - Xia, Xin; Yates, Jane L. R.; Jones, Glenn; Sarwar, Misbah; Harkness, Ian; Thompsett, David
Abstract : (Left) The atomic model of oxygen adsorption on the MX supported Pt overlayer film. (Right) Support material selection through the Pt wetting ability parameter δ and oxygen binding energy, Δ E *[O]. The dashed line corresponds to the wetting parameter δ 0 of the unsupported Pt(111) surface. The red line denotes the apex of ORR activity. Abstract : In this work, a range of corrosion resistant materials have been assessed for their suitability as Pt catalyst supports using density functional theory. The influence of support materials on the catalytic activity has been disentangled into geometric and electronic effects via a correlation between the d-band centre of the supported Pt film and the interfacial lattice strain (lattice match). Two energetic descriptors, the Pt wetting parameter and the relative oxygen binding energy, have been used to describe the catalyst–support adhesion behaviour and the resultant activity. Taking both of the factors into account, some novel candidate materials, e.g. TiC and WC, are recommended as catalyst supports.